Employing sensory marketing as a promotional advantage for creating brand differentiation and brand loyalty - Ibn e Hassan; Jawad Iqbal (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2016)
Sensory marketing is an up-coming tool that integrates the five human senses for generating a total experience that the customer keeps in mind. The main objective of the study is to identify the impact of sensory marketing on consumers to generate brand loyalty. The second objective of this study is to generate impact of sensory marketing on brand loyalty and also brings out the results, which can be adopted by marketers for the other products of same genre. The third objective is by using the sensory marketing to gain promotional advantage over competitors. SPSS 21 is used in this study. Random sampling is used to collect the data. Sample size is of 520 and 5- point Likert scale is used. The result of the study shows that the effective usage of the sensory marketing generates the brand differentiation and brand loyalty in the form of sale enhancement. Marketing manager can attain promotional advantage and retain the loyal customer by using sensorial environment.
Keywords: 330; brand differentiation; brand loyalty; sensory marketing; customer